2021
DOI: 10.1108/ijshe-08-2020-0320
|View full text |Cite
|
Sign up to set email alerts
|

Intention to adopt pro-environmental behaviors among university students of hard and soft sciences: the case of drinking by reusable bottles

Abstract: Purpose The market of bottled water is one of the largest in the world. Paradoxically, the consumption of water in plastic bottles is highest in countries rich in the potable tap water of excellent quality. This paper aims to gain a better understanding of the factors that foster or hinder the intention to use refillable water bottles by university students and to determine whether their study program played a moderating role. Design/methodology/approach Within the framework of Ajzen’s theory of planned beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…The finding of H4 with a significant positive beta value in this analysis illustrates that high schoolers' tendency to environmental behavior intentions increases with increasing environmental physics understanding. This finding strongly supports previous research, which states that environmental physics understanding contributes to individual environmental behavior intentions (Fröhlich et al, 2013;Fedi et al, 2021).…”
Section: Resultssupporting
confidence: 92%
“…The finding of H4 with a significant positive beta value in this analysis illustrates that high schoolers' tendency to environmental behavior intentions increases with increasing environmental physics understanding. This finding strongly supports previous research, which states that environmental physics understanding contributes to individual environmental behavior intentions (Fröhlich et al, 2013;Fedi et al, 2021).…”
Section: Resultssupporting
confidence: 92%
“…As this variable is based on an individual's perception about both personal and environmental factors that would facilitate or hinder their ability to perform a behavior, the TPB is superior to the TRA in predicting behaviors in more specific and complicated contexts (Ajzen, 1991). Previous studies have applied the TPB and confirmed the usefulness of this model in predicting both intention to recycle (Taylor and Todd, 1995;Mannetti et al, 2004;Greaves et al, 2013;Botetzagias et al, 2015;Wan et al, 2017;Passafaro et al, 2019;Tian et al, 2019;Fedi et al, 2021) and recycling behavior (Tang et al, 2011;del Aguilar-Luzón et al, 2012;Onel and Mukherjee, 2017;Passafaro et al, 2019). Based on these studies, the following hypotheses are proposed: H1a: Subjective norms positively predict waste management behavior.…”
Section: Theory Of Planned Behavior and Its Application In Waste Mana...mentioning
confidence: 99%
“…The prediction of the SC behaviour is another topic and some authors used psycho-behavioural sciences to explain human behaviour [34]- [36]. Also face to face interviews and descriptive survey methods were used to better understand the students SC behaviour in specific circumstances [37], [38].…”
Section: Identification Of the Main Topics To Teaching Andmentioning
confidence: 99%